Advanced Computational Methodologies Used in the Discovery of New Natural Anticancer Compounds - Chavda, Vivek P.; Ertas, Yavuz Nuri; Walhekar, Vinayak; Modh, Dharti; Doshi, Avani; Shah, Nirav; Anand, Krishna; Chhabria, Mahesh (Frontiers in Pharmacology, 2021)
Natural chemical compounds have been widely investigated for their programmed necrosis causing characteristics. One of the conventional methods for screening such compounds is the use of concentrated plant extracts without isolation of active moieties for understanding pharmacological activity. For the last two decades, modern medicine has relied mainly on the isolation and purification of one or two complicated active and isomeric compounds. The idea of multi-target drugs has advanced rapidly and impressively from an innovative model when first proposed in the early 2000s to one of the popular trends for drug development in 2021. Alternatively, fragment-based drug discovery is also explored in identifying target-based drug discovery for potent natural anticancer agents which is based on well-defined fragments opposite to use of naturally occurring mixtures. This review summarizes the current key advancements in natural anticancer compounds; computer-assisted/fragment-based structural elucidation and a multi-target approach for the exploration of natural compounds.